High school mathematics teachers’ competence on the contents of a quantitative research paper - Lany D. Dullas; Samuel R. Soliven (International Journal of Evaluation and Research in Education (IJERE), 2021)
Competence in research is an attractive feature that should be established for all practitioners because specialists with training and expertise in research will recognize strategic thinking, interpretation, and synthesizing more easily. Hence, this study aimed to describe the knowledge competency among junior high school mathematics teachers on the research processes applied on the contents of the various sections of a quantitative research paper. The descriptive method of research has been used to characterize the knowledge competence of 108 junior high school teachers on the research processes. The study used the research skill test, which was a researcher-made instrument, consisting of 50 multiple choice items with four choices each. The instrument went through the process of validity and reliability analysis obtaining a good result of 0.81. This study revealed that they were “novice” or had achieved the learning level of competency on the research processes applied on the contents of the different parts of a quantitative research paper. More so, they identified that interpretation of statistical results was a challenging part of doing a research paper.